Chronotype and circadian rhythm in bipolar disorder : a systematic review - Melo, Matias C. A. (2016)
Despite a complex relationship between mood, sleep and rhythm, the impact of circadian disruptions on bipolar disorder (BD) has not been clarified. The purpose of this systematic review was to define current evidence regarding chronotype and circadian rhythm patterns in BD patients. 42 studies were included, involving 3432 BD patients. Disruption of the biological rhythm was identified, even in drug-naïve BD patients and independently of mood status. Daily profiles of melatonin levels and cortisol indicated a delayed phase. Depression was more frequently associated with circadian alterations than euthymia. Few studies evaluated mania, demonstrating irregular rhythms. Evening type was more common in BD adults. Studies about the influence of chronotype on depressive symptoms showed conflicting results. Only one investigation observed the influences of chronotype in mania, revealing no significant association. Effects of psychoeducation and lithium on rhythm in BD patients were poorly studied, demonstrating no improvement of rhythm parameters. Studies about genetics are incipient. In conclusion, disruption in circadian rhythm and eveningness are common in BD. Prospective research evaluating the impact of circadian disruption on mood symptoms, metabolism, seasonality, the influence of age and the effects of mood stabilizers are needed.